Contact Languages in the Post- Soviet Space: Linguistic and Cultural Dominance - E. V. Voevoda (Vestnik MGIMO-Universiteta)
The article addresses the sociopolitical and linguistic problems in choosing contact languages for communication in the post-Soviet space. The author analyses the factors that determine the status of a contact language and its impact on the choice of partners in political, economic and cultural spheres.